Just before sewing needles. A functional hypothesis for Gravettian Noailles-type burins from Isturitz cave (Basque Country, southwestern France). (June 2019) - Calvo, Aitor; Perales, Unai; García-Rojas, Maite; Normand, Christian; Arrizabalaga, Alvaro
Abstract: This paper presents the results achieved in the technological, typometric, morphotypological and, mainly, use-wear analysis (supported by an experimental programme) of the collection of Noailles burins from level IV of Isturitz cave. The data obtained revealed that this type of burin was a highly standardised tool; thus, it is a small morphotype, generally made from a very narrow bladelet, usually on an oblique and concave truncation. This created a sharp active zone (the dihedral) where the use-wear traces are normally located. Their distribution shows that these burins were used mainly for piercing, while the faintness of the traces suggest that they were employed with quite soft materials, such as dry hide. Experimentation demonstrated the effectiveness of these implements for piercing dry hide, and the use-wear on the experimental burins correspond to the traces observed on archaeological burins. It also showed that the Noailles burins of Isturitz Cave are incompatible with harder materials or tasks of longer duration or intensity. Highlights: Noailles-type burins are highly standardised tools, intended for specialized and precision tasks. Noailles-type burins of Isturitz cave were probably use for piercing soft materials such as dry hide. The effectiveness of Noailles-type burins for piercing activities (especially on soft materials) is very high. In this case study, the systematic work of hard materials (such as bone, antler or wood) must be ruled out.